Effect Of Nitrohumic Acid Derived From Low-Rank Coal Of Sarawak On Growth Of Brassica Oleracea Sp. - Zulfaqar, bin Sa'adi (Faculty of Resource Science and Technology, 2008)
Humic acid derived from low rank coal of Mukah prepared using alkaline extraction method was referred as nitrohumic acid. Nitrohumic acid was characterized for moisture content, ash content, nitrogen content, total acidity, carboxyl groups and phenolic group. Spectroscopy characterization was conducted using FTIR spectroscopy, UVIVis spectroscopy and CHN Analyzer. Optimization study conducted to invesli~ate the role of the nitrohumic acids to improve leafy vegetable growth of Brassica Oferacea sp. by using different level of nitrohumic acids dosage and three types of soil was used namely peat soil, sandy soil and laterite soil. Growth of Brassica Oferacea ~p. had been monitored for 51 days. The effects of nitrohumic acids on the aggregate stability are dependent on the soil type. Growth of Brassica Oferacea sp. was improved by 24% and 39% by addition 50g and 100g of nitrohumic acids for peat soil and 23% to 30% for sandy soil, while laterit soil was not favorable for the growth of Brassica Oferacea sp. Water holding capacity for sandy soil were 4% to 9%, 25% to 36% for peat soil and 20% to 28% for laterite soil. Soil organic matter content was improved by 7 to 17% with the application of different levels of nitrohumic acids as compared to control in peat soil, 8% to 188% in sandy soil and 0.8% to 9% in laterite soil.